International study to develop a patient-reported outcome measure to evaluate outcomes of gender-affirming care - the GENDER-Q - Manraj N. Kaur; Shane D. Morrison; Shelby L. Kennedy; Tim C. van de Grift; Astrid Højgaard; Amalie Lind Jacobsen; Natasha Johnson; Margriet G. Mullender; Lotte Poulsen; Thomas Satterwhite; Richard Santucci; John Semple; et al. (SpringerOpen, 2024)
Abstract Background To meaningfully understand outcomes of gender-affirming care, patient-reported outcome measures (PROMs) that are grounded in what matters to individuals seeking care are urgently needed. The objective of this study was to develop a comprehensive PROM to assess outcomes of gender-affirming care in clinical practice, research, and quality initiatives (the GENDER-Q). Methods Internationally established guidelines for PROM development were used to create a field test version of the GENDER-Q. In-depth interviews were conducted from December 2018 to March 2020 with youth and adults aged 16 years and older who were seeking or had received gender-affirming care at outpatient clinics providing gender-affirming care located within tertiary care centers or communities in Canada, Denmark, the Netherlands or the US. Data were analyzed and used to develop a conceptual framework and an item pool, which was used to develop preliminary scales. Between February 2021 to November 2021, iterative feedback was sought from clinicians and patient participants on the scales and used to refine or develop new scales. The revised scales were pilot-tested using a crowd-sourcing platform between February 2022 and April 2022. Results Data from interviews with 84 participants (aged 34 ± 14 years) resulted in a conceptual framework of the GENDER-Q with 13 domains measuring health-related quality of life, sexual, urination, gender practices, voice, hair, face and neck, body, breasts, genital feminization, chest, genital masculinization, and experience of care. Preliminary versions of 44 scales were developed covering most concepts in the conceptual framework. Iterative feedback was obtained from clinician experts (4 to 37 experts per scale; response rate, 67%) and 7-14 patient participants (depending on scale). All scales were refined, and 15 new scales were developed, resulting in 55 scales in the field test version of the GENDER-Q. In total, 601 transgender and gender diverse (TGD) people (aged 25 ± 6 years) participated in the pilot field test and the data were used to make changes to the field test survey. Conclusion The GENDER-Q was developed using extensive input from TGD individuals and clinician experts and represents the most comprehensive set of independently functioning scales that are available to date. An international field test of the GENDER-Q was completed in 2024 and the GENDER-Q is available for use in patient care, clinical research and quality improvement efforts.